A change of maintenance of mobile phosphorus in the genetic horizons of ordinary black-earth - Крамарьов, С. М.; Крамарьов, О. С.; Христенко, А. О.; Токмакова, Л. М.; Жученко, С. І.; Сироватко, В. А.; Цьова, Ю. А.; Сироватко, К. В. (Scientific Progress & Innovations, 2015)
Ordinary black-earthes on the loess type of heavy composition of North Steppe of Ukraine contain the promoted amount of apatites compounds. As a result the use of any acid methods (as GOST 26204-91 (Chirikov’s method)) has as a result the substantial artificial overstating of estimation of the phosphatic state of soils (on 40–80 mg of Р2О5/kg of soil). For diagnostics of the phosphatic state of these soils, in obedience to the requirements of normative documents of Ukraine, it follows to use the followings standards: DSTU 4114 (Machigin’s method), DSTU 4727 (method of Karpinskyi- Zam’yatina) and DSTU ISO 11263 (Olsen’ method). For the receipt of high harvests with high quality on ordinary black-earthes of North Steppe of Ukraine it is necessary to bring in not less phosphoric fertilizers, than on other soils of country based on information of the ground diagnostics.